2016
DOI: 10.1002/mren.201600022
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Modeling of Mixing Behavior in a 3D Atom Transfer Radical Copolymerization Stirred-Tank Reactor

Abstract: Multiscale mixing phenomena in stirred‐tank polymerization reactors are mainly caused by stir agitation, which performs a key function in macroscopic and microscopic flow fields. Both macroscopic and microscopic flow fields interact with each other and significantly affect the microstructure and product distribution of the resultant polymers. In this work, a computational fluid dynamics model combining the moment method used in the polymerization engineering field is implemented and validated using open data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The selectivity and yield of reactions depend strongly on the hydrodynamics in STRs. However, little simulation works focuses on the yield or the distribution of product in agitated reactors, which is associated with a reaction process . The present work shows its emphasis on the species distribution in a reaction process associated with the hydrodynamics in STRs.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The selectivity and yield of reactions depend strongly on the hydrodynamics in STRs. However, little simulation works focuses on the yield or the distribution of product in agitated reactors, which is associated with a reaction process . The present work shows its emphasis on the species distribution in a reaction process associated with the hydrodynamics in STRs.…”
Section: Introductionmentioning
confidence: 97%
“…However, little simulation works focuses on the yield or the distribution of product in agitated reactors, which is associated with a reaction process. 48 The present work shows its emphasis on the species distribution in a reaction process associated with the hydrodynamics in STRs. A kinetic model of the phenylboronic acid ester production process is firstly derived using the power law analysis on the basis of experimental data and then loaded into the CFD software to simulate the reaction process for the phenylboronic acid ester production in the STR.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a polymerization process, the molar mass distribution (MMD) of polymeric species type (e.g., unsaturated chains) may evolve as (reaction) time progresses and may depend on the physical location inside a chemical reactor vessel due to, e.g., nonideal (slow) reactor mixing. [3][4][5][6] Because of the dynamics of systems with distributions, a model, i.e., a mathematical description of the chemical, physical, mechanical and electrical phenomena taking place, is often a prerequisite for analysis and control. Notably, in the past two decades, stochastic solvers have risen to prominence in many engineering science fields.…”
Section: Introductionmentioning
confidence: 99%
“…This reality led toward the application of computational fluid dynamics (CFD) simulation on reaction engineering. The reliability and predictability of CFD tool for design and scale‐up of polymerization reactor has been proved by many researchers 18–36 . Many CFD simulations have been conducted to investigate the hydrodynamic behavior in reactors, 19,20,22–25 whereas only a few studies took polymerization kinetics into account in numerical simulation.…”
Section: Introductionmentioning
confidence: 99%
“…The reliability and predictability of CFD tool for design and scale-up of polymerization reactor has been proved by many researchers. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Many CFD simulations have been conducted to investigate the hydrodynamic behavior in reactors, 19,20,[22][23][24][25] whereas only a few studies took polymerization kinetics into account in numerical simulation. Among these limited literatures, Kolhapure and Fox 21 utilized CFD to simulate ethylene polymerization in a tubular reactor and found that the imperfect mixing of reaction system would result in the appearance of local hot spots, decrease of conversion, and increase of dispersity.…”
mentioning
confidence: 99%